Modelling hysteresis in vanadium dioxide oscillators. Issue 11 (1st May 2015) - Maffezzoni, P.; Daniel, L.; Shukla, N.; Datta, S.; Raychowdhury, A.; Narayanan, V.
Abstract : An original circuit‐level model of two‐terminal vanadium dioxide electron devices exhibiting electronic hysteresis is presented. Such devices allow realisation of very compact relaxation nano‐oscillators that potentially can be used in bio‐inspired neurocomputing. The proposed model is exploited to determine the parameters, values that ensure stable periodic oscillations.